Population Dynamics of an Indigenous Carp (Labeo dussutnieri) of the River Pampa, Kerala (India) - B., Madhusoodana Kurup (Fishery Technology, 2025)
Based on length composition of commercial landings of Labeo dussumieri of the river Pampa, growth parameters, La and K were estimated using ELEFAN I programme as 464.7 mm and 0.64/anmm respectively in male and 502 mm and 0.81/ annum in female. Average instantaneous rates of mortality Z, M and F in male were respectively 1.4305, 0.8595 and 0.5710 while in females the above values were 2.3348, 1.0863 and 1.2485. From the length converted cohort analysis, F was estimated to be 0.5709 in male against 1.2484 in female. The results of the present study showed that males of L dussumieri of the river Pampa are harvested below the optimum level while the females are exploited at optimum level and therefore, it is concluded that the stock of this species can be maintained at a sustainable level at the present level of exploitation.